Analisis penentuan harga jual bibit - Syahfitri, Rika (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this investigation is to examine the approach used in setting the selling price of CV. Prakaga and assess the suitability of the existing selling price with the method. In this study, we employ a Cost Plus Pricing strategy, which involves arriving at a selling price by summing the manufacturing costs and the resulting margin. The research methodology used includes qualitative and quantitative approaches. The full cost method was used in determining the cost of goods sold through the application of quantitative analysis. The findings show that the use of the full cost method is superior as it includes all production-related costs incurred in each process. Notably, there is a visible difference in the respective amounts generated by the firm method and the full cost method, where the firm method generates less cost than the full cost method. From this it can be concluded that CV. Prakaga in determining the selling price, should use a way that can achieve the expected profit and avoid losses in the event of a decrease in sales or consumer interest.